The efficacy of using the allogeneic osteoplastic material in skull trepanation - A. A. Ofitserov; N V. Borovkova; A. E. Talypov; O. V. Leshchinskaya; N. E. Kudryashova; A. S. Mironov; M. S. Makarov; I. N. Ponomarev; A. S. Kozhanov; A. A. Budaev (Трансплантология (Москва))
Introduction. When performing osteoplastic craniotomy, there is a need to fill the diastasis between the skull bone and the explanted bone fragment. Grafts based on allogeneic bone chips and collagen (bone-plastic material) may be very effective for cranial bone repair in diastasis area.Aim. To evaluate the safety and clinical efficacy of osteoplastic material during the osteoplastic craniotomy.Material and methods. A retrospective and prospective clinical study was conducted at the N.V. Sklifosovsky Research Institute for Emergency Medicine and included 12 patients treated in Urgent Neurosurgery Department with diagnoses suggesting the need for craniotomy. Allogenic osteoplastic material was obtained from a 0.7-0.9% solution of type I collagen and spongy bone chips with a fraction size of 315-630 microns. Osteoplastic material grafts were used intraoperatively at the cranioplastic stage of the operation after the main stages had been completed. The efficacy and safety of the use of osteoplastic material were evaluated clinically and radiologically in the early postoperative period.Results. In the early postoperative period, the study patients had no pyo-septic complications, severe pain or soft tissue swelling. All patients were discharged from the hospital in satisfactory condition to be followed-up by the physician or neurologist at the out-patient facility. The computed tomography performed in the early postoperative period visualized the diastasis lines along the bone flap line in the comparison group patients (without osteoplastic material); and in the main group, the osteoplastic material was clearly visualized. At computed tomography of the skull performed after 6–9 months and after 2–18 months, the signs of bone tissue consolidation were visualized in the patients of the main group. The radiodensity of the autologous bone flap in both groups did not significantly change at any periods. In the diastasis area, the radiodensity of diastasis in the main group was significantly higher than in the comparison group. After 1-1.15 years the radiodensity values in the diastasis area increased by average of 1.95 times (p<0.05) in the patients of the main group, while in the patients without osteoplastic material, this parameter did not significantly change during the entire follow-up period.Conclusions. In patients with intraoperative cranioplasty osteoplastic material grafts did not cause complications in the early and late postoperative period. Intraoperative cranioplasty performed with using osteoplastic allogeneic material caused no complications in either early or late postoperative periods. The presence of osteoplastic material contributed to the consolidation of the autologous bone flap and healthy bone.